Aplicativo móvel para o acompanhamento do nível de oxigênio (SpO2) no sangue de pacientes neonatais e adultos - Silva, Pedro Henrique Aires da (Universidade Federal Rural do Semi-Árido, 2020)
This work proposes to develop a software application designed to assist health professionals who work with patients who need constant monitoring of the amount of oxygen present in the blood. The rate of oxygen present in the blood is an extremely important vital sign for patients in the ICU, in outpatient and neonatal sectors. The present work seeks to develop the modeling of the system, making use of the UML language, showing its functional requirements, also using Use Case diagram, as well as interface prototypes, which allows to have a more real view of the final project. It also shows a survey that was applied to 42 health professionals who deal with the scenario of patients in hospitals on a daily basis. Such research was carried out in order to survey functional requirements for the application. Finally, the development of the application for smartphones that have the Android or iOS operating system using React-Native as a tool for its development.
Keywords: Inovação; Saúde; Desenvolvimento; Android; Innovation; Health; Development; Android; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO